Overview of Potential Use of Hydroxyl and Hydrogen as an Alternative Fuel in Colombia - Forero, Natalia Duarte; Barrios, Donovan Arango; Forero, Jorge Duarte (International Journal of Energy Economics and Policy, 2019)
In the Paris agreement about climate change, it was established that greenhouse gas emissions must be reduced by 0% in order to avoid irreversible damage, so the world economy based on fossil fuels must undergo a transformation towards an economy clean, safe and sustainable. As a result, it has been established that the only alternative that guarantees 0% emissions of polluting gases is the economy of hydrogen. Countries such as the Netherlands, the United States, and the European Union have projected policy towards 2050 that expects to meet the objectives set out in the Paris agreement. In this document shows the different alternative fuels that are currently being proposed to mitigate polluting emissions, as well as the overview of these fuels in Colombia, and how, from the different renewable energy sources that this country has, could venture economically and politically towards economy based on the use of hydroxy and hydrogen as a raw material and energy source, showing its possible applications. The foregoing will allow to identify the potential of application of these fuels in the energy matrix of Colombia and define policies to accelerate their implementation. Keywords: Environmental Pollution, Energy Policy, Alternative Fuels, Hydrogen, Renewable Energy. JEL Classifications: L78, L90, O31, Q20 DOI: https://doi.org/10.32479/ijeep.8395